Incentive and welfare effects of correlated returns. Issue 1 (3rd November 2020) - Courbage, Christophe; Peter, Richard; Rey, Béatrice
Abstract: We provide a microeconomic analysis of the incentive and welfare effects of correlated returns. While most of the existing literature has focused on risky returns as an aggregate shock, we introduce a correlation between returns and the individual's nonfinancial endowment. Using a simple consumption‐saving model with two periods, time‐separable utility, and two states allow us to rewrite the correlated return in terms of a transfer rate that measures the spread between the return in the good and the bad state. We find that a critical level of the transfer rate separates savers from borrowers. We also identify restrictions on the individual's risk preferences for a larger transfer rate to raise optimal savings. We analyze the welfare effects of correlated returns by characterizing the transfer rate that maximizes intertemporal expected utility. The welfare benefits of correlated returns derive from their insurance effects.